2023
DOI: 10.3390/jof9010097
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Profiling of Different Antrodia cinnamomea Phenotypes

Abstract: Antrodia cinnamomea (AC) is a precious medicinal fungus with numerous therapeutic benefits. Based on the color appearance of its fruiting bodies, AC can be divided into red AC (RAC), yellow AC (YAC), and white AC (WAC); however, the differences in their metabolomic profiles remain unknown. This study aimed to analyze the metabolomic profiles of three different AC phenotypes and examine their relationship to the color appearance of fruiting bodies. The results showed that although RAC, YAC, and WAC appear to ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The appearance of fruiting bodies is generally red-orange, but in certain regions of Taiwan, rarely yellow and white variants also occur. Metabolomic Profiling indicated that red AC possesses relatively higher contents of triterpenoids and diverse metabolites than yellow AC and white AC ( Su et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…The appearance of fruiting bodies is generally red-orange, but in certain regions of Taiwan, rarely yellow and white variants also occur. Metabolomic Profiling indicated that red AC possesses relatively higher contents of triterpenoids and diverse metabolites than yellow AC and white AC ( Su et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…It features a sporangium on the surface of the fruiting body that contains spores, an uneven surface, and a safrole odor. Based on the color of fruiting bodies, the fungi are classified as red, yellow, and white A. cinnamomea (Su, et al, 2023). Triterpenoids and polysaccharides are the primary active components of A. cinnamomea (He et al, 2019;Liu et al, 2004).…”
Section: Introductionmentioning
confidence: 99%